Approximation by fourier sums and best approximations on classes of analytic functions - Serdyuk, A. S.; Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish asymptotic equalities for upper bounds of approximations by Fourier sums and for the best approximations in the metrics of C and L1 on classes of convolutions of periodic functions that can be regularly extended into a fixed strip of the complex plane.